Mastering Financial Accounting Essentials: The Critical Nuts and Bolts (Wiley Finance) - McCrary, Stuart A. (Wiley, 2012)
This book presents material in a way that explains the key features of modern accounting step by step and helps you develop an intuitive understanding of accounting.